MENELUSURI JEJAK DAN KIPRAH KIAI KHOLIL AL-BANGKALANI - Aah Syafaah (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
Kiai Kholil is a scholar of international scale and a pivot of power for the synergy of the scholars network of santri. Specifically, in the land of Madura and Tapal Kuda ranging from Situbondo, Banyuwangi, Probolinggo and Bondowoso with the network of Pesantren Sidogiri Pasuruan and Talangsari Jember. By this coordination he succeeded to gather those social groups through the Sabilillah-Hizbullah laskar which also connected the kinship line of his predecessors. He was able to capture the hidden potentials behind the land and Madurese community, as Snouck Hurgronje had assessed as central to the network of scholars of santri in Java. This paper intends to trace the life of Kiai Kholil Al-Bangkalani as one of the influential clerics of his time. The influence was built not only by the kinship line it possesses, but also pioneered with great soul and expertise in various sciences and studies of social religious fields of society. His thoughts were contained in a number of works that continue to adorn the treasury of science from the past until today.Keywords: Thought, Madurese, Ulama, Kiai Kholil